Antisense Oligonucleotides Capable of Promoting Specific Target mRNA Reduction via Competing RNase H1-Dependent and Independent Mechanisms - Vickers, Timothy A.; Crooke, Stanley T. (PLOS ONE, 2014)
Antisense oligonucleotides (ASOs) are most commonly designed to reduce targeted RNA via RNase H1-dependent degradation. In this paper we demonstrate that cellular proteins can compete for sites targeted by RNase H1-dependent ASOs. We further show that some ASOs designed to mediate RNase H1 cleavage can, in certain instances, promote target reduction both by RNase H1-mediated cleavage and by steric inhibition of binding of splicing factors at a site required for efficient processing of the pre-mRNA. In the latter case, RNase H cleavage was prevented by binding of a second protein, HSPA8, to the ASO/pre-mRNA heteroduplex. In addition, using a precisely controlled minigene system, we directly demonstrated that activity of ASOs targeting sites in introns is strongly influenced by splicing efficiency.